A Retrospective Study of the Prevalence of First Premolars in 306 Thoroughbred Yearlings. (June 2019) - Tanner, R. Brad
The equine first premolar is now considered a vestigial tooth that does not play a role in mastication. For centuries, this tooth has been blamed for a number of abnormalities. Given its anatomical location, the tooth is often implicated by riders to cause biting issues. Treatment of this tooth is considered controversial, with some clinicians extracting all equine first premolars prior to bit introduction and others choosing to remove only those shown to cause bite-related problems. In a private veterinary hospital in Lexington, Kentucky, dental charts of 306 Thoroughbred yearlings, average age 14.73 months (range: 8-22.7 months), were reviewed. In this group, 72.9% of horses, average age 14.99 months, had erupted first premolars at the time of the examination. This percentage increased with age, and by 18 months, 90% of Thoroughbred yearlings had erupted maxillary first premolars. Sexual dimorphism is present in the study group, as significantly fewer males than females have first premolars at 67.4% and 77.6%, respectively, P ≤ .05. Mandibular and supernumerary first premolars are rarely reported in the literature and were not present in this group, suggesting they may erupt at a later age or are less common in Thoroughbreds. Maxillary first premolars are common in Thoroughbred yearlings and continue to erupt to 18 months of age in this breed, later than previously reported in some text.